2020
DOI: 10.3390/cancers12123707
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Patients with NSCLC and Brain Metastases Treated with Immune Checkpoint Inhibitors in a ‘Real-Life’ Setting

Abstract: There is lack of data addressing the intracranial (IC) efficacy of immune checkpoint inhibitors (ICIs) on brain metastases (BM) in non-small cell lung cancer (NSCLC). This patient category is underrepresented in randomized clinical trials. We retrospectively collected clinical data on patients with non-oncogenic driven NSCLC with BM who were treated with ICIs at two medical oncology institutes in Sweden and Greece from 2016 to 2019. IC efficacy was assessed in patients who had not received local treatment for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
3
7
0
Order By: Relevance
“…Moreover, the discordance of treatment response between intracranial and extracranial lesions should also be noted. The discordance rate was 15.8% in our study, which was consistent with other previous studies ranging from 12.7% to 36.4% ( 16 , 33 , 34 ). The reason for the discordant outcome may be the difference in the tumor microenvironment between primary tumors and BMs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, the discordance of treatment response between intracranial and extracranial lesions should also be noted. The discordance rate was 15.8% in our study, which was consistent with other previous studies ranging from 12.7% to 36.4% ( 16 , 33 , 34 ). The reason for the discordant outcome may be the difference in the tumor microenvironment between primary tumors and BMs.…”
Section: Discussionsupporting
confidence: 93%
“…Another tumor characteristic affecting patient outcomes is disease burden. We found that a high disease burden, defined as three or more metastatic organs, was an independent negative predictor for both intracranial and extracranial PFS, which is consistent with previous studies ( 33 ).…”
Section: Discussionsupporting
confidence: 92%
“…Another important nding of our study was that only 32% of patients showed concordant outcomes between intracranial and extracranial responses. The discordant rate was 20%, which was similar to those reported in previous studies (22% (Goldberg et al 2020) and 24% (Skribek et al 2020)). One possible explanation of the discordance is the genetic distinction between the primary disease and brain metastatic lesions.…”
Section: Discussionsupporting
confidence: 90%
“…The role of ICIs in BM has been studied in retrospective analysis, case series, and preliminary clinical trials. These discoveries and their quick translation into clinical practice are causing significant shifts in treating patients with BM from NSCLC ( 85 ). Multiple studies have consistently shown that ICIs improve overall survival in both primary tumors and BM, supporting the utility of ICIs in the treatment of BM ( 88 ).…”
Section: Recent Advancements In the Treatment Of Bm From Nsclc With I...mentioning
confidence: 99%